Damage detection through bilinear stiffness estimation in multi-degree-of-freedom frame structures - Garrido, Carlos Hernán (2014)
During its lifetime, the integrity of structures may be affected by exposure to dynamic loads such as earthquakes. In these cases, structures might become damaged, and an early overall evaluation of their integrity is necessary. A particular pattern of damage is that produced by the existence of breathing cracks. These cracks are characterized by their opening and closure during the oscillation of the cracked structural element. In this paper, it is proposed a method for detection of breathing cracks in multi-degree-of-freedom frame structures. The method is based on bilinear stiffness direct estimation, individually for each story of the structure, by using a least-squares approach. The proposed method is demonstrated through a numerical example using the FEM to model a planar structure which presents several breathing cracks. The results suggest that this approach is more sensitive and precise than approaches based on linear stiffness models in detecting and localizing damage due to breathing cracks.